Assessing global fisheries using Fisheries Performance Indicators: Introduction to special section. (March 2021) - Eggert, Håkan; Anderson, Christopher M.; Anderson, James L.; Garlock, Taryn M.
Abstract: This special section of Marine Policy is devoted to applications of the Fisheries Performance Indicators (FPIs). The overall objective of these indicators is to provide a low cost, easily accessible and rapid assessment tool that measures an overall status of a particular fishery anywhere in the world where all three sustainability pillars; ecology, community, and economics are considered [2] . The eight case studies that follow this introduction are the result of a collaboration between researchers at the Institute for Sustainable Food Systems at the University of Florida, researchers and colleagues around the world and the Environment for Development (EfD) Global Hub at University of Gothenburg. EfD is a global network of environmental economics research centers aiming at effective management of the environment in the Global South. The rest of this introduction is organized in the following manner. The next section gives a brief introduction to FPIs, the third section provides a quick background to EfD, its Marine research program and how the FPIs were developed, Section 4 has an overview and some descriptive data from the 149 fisheries currently in the FPI data base, Section 5 gives an overview of the eight new case studies, and the last section concludes.